Web-based management information system of reverse supply chain. (13th February 2009) - Zhigang, Jiang; Xuhui, Xia; Huanxiao, Hu
Reverse supply chain is a new management mode to win competition for enterprises; information system is an effective tool to support the implementation of reverse supply chain management in enterprises. A system structure was set up and the information integration model was put forward based on the web, and then the operating mechanism of reverse supply chain was elaborated.